2003
DOI: 10.1046/j.1365-313x.2003.01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between two cis‐acting elements, ABRE and DRE, in ABA‐dependent expression of Arabidopsis rd29A gene in response to dehydration and high‐salinity stresses

Abstract: SummaryMany abiotic stress-inducible genes contain two cis-acting elements, namely a dehydration-responsive element (DRE; TACCGACAT) and an ABA-responsive element (ABRE; ACGTGG/TC), in their promoter regions. We precisely analyzed the 120 bp promoter region (À174 to À55) of the Arabidopsis rd29A gene whose expression is induced by dehydration, high-salinity, low-temperature, and abscisic acid (ABA) treatments and whose 120 bp promoter region contains the DRE, DRE/CRT-core motif (A/GCCGAC), and ABRE sequences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
428
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 663 publications
(448 citation statements)
references
References 43 publications
15
428
0
5
Order By: Relevance
“…Contrary to our results, Narusaka et al (2003) showed that artificial reporter constructs in which all cis elements apart from the DRE (CRT) elements were eliminated, fail to be activated by ABA treatment, indicating that this element cannot, in isolation, respond to ABA (Narusaka et al, 2003). However, this lack of response to ABA is consistent with data from the same laboratory that indicated CBF1-4 are not ABAresponsive.…”
Section: Discussionsupporting
confidence: 62%
“…Contrary to our results, Narusaka et al (2003) showed that artificial reporter constructs in which all cis elements apart from the DRE (CRT) elements were eliminated, fail to be activated by ABA treatment, indicating that this element cannot, in isolation, respond to ABA (Narusaka et al, 2003). However, this lack of response to ABA is consistent with data from the same laboratory that indicated CBF1-4 are not ABAresponsive.…”
Section: Discussionsupporting
confidence: 62%
“…A5 and BS, Expressing the TaCHP transgene; C13, negative control (empty vector only). AtRD29A promoter, and the two pathways coactivate the expression of AtRD29A (Narusaka et al, 2003). In Figure 9, we present the model we have elaborated to describe the function of TaCHP.…”
Section: Tachp Is Involved In An Aba-dependent Pathwaymentioning
confidence: 99%
“…The latter is mediated mainly through an IP3-Ca 2+ -DREB cascade (Zhu, 2001), while the former involves AREB and other modules. Both pathways require participation of many regulatory factors (Chinnusamy et al, 2004), and there is a degree of cross talk between the two pathways (Haake et al, 2002;Narusaka et al, 2003). However, the detailed characteristic of the cross talk is still not well dissected.…”
mentioning
confidence: 99%
“…MYB, CBF/DREB1, HSF, TGA6, BOS1, bZIP, AP2/EREBP etc. are indicated for their role in plant development and stress tolerance (Meshi and Iwabuchi 1995;Xiong et al 1997;Kizis et al 2001;Narasuka et al 2003;Mengiste et al 2003).…”
Section: Introductionmentioning
confidence: 99%